Design and Implementation of a RF Energy Harvesting Module with DC Power Control - Partal, Hakan P.; Partal, Sibel Zorlu; Belen, Mehmet A. (IEEE, 2018)
In this experimental research paper, a zero-bias RF energy rectifying antenna (rectenna) is designed at an ISM band, DC output is amplified by employing DC boost converters, and DC energy is stored on super-capacitors. The rectenna is analyzed for low power detection and rectification efficiencies, impedance matching network is implemented to reduce the reflected RF power at the rectifiers' input, DC to DC converters are evaluated for their compatibility to the rectifiers, and super-capacitor behaviors are investigated for their charging time and adaptability as wirelessly chargeable batteries. Many practical concerns and experiences are discussed for the RF energy harvesting systems' potential implementations on low power sensors and wireless communications network.
Keywords: RF energy harvesting; rectenna; Schottky rectifier; RFID; wireless power transfer; Engineering; Telecommunications